APLIKASI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFI UNTUK PENENTUAN LOKASI TEMPAT PENAMPUNGAN SEMENTARA SAMPAH DI KOTA MAGELANG - , TITIK DWI WAHYUNI, Dr. R. Suharyadi, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Temporary waste is necessary in order to solve the waste problem. Fasilities of TPS in Magelang is still needed because the existing TPS insufficient and the location is not appropriate. The purpose of this study is (1) remote sensing image analysis capabilities in data acquisition factors are used to estimate the volume of waste in the city of Magelang, (2) to determine the best locations of temporary waste in Magelang city using Geographic Information System (GIS). The factors used to estimate the volume of waste obtained from interpretation of high resolution imagery, Worldview imagery and field checks. Calculation of the average of garbage volume daily in Magelang city is done directly in the field by calculating garbage volume generated each block per day. Determination of location of the temporary waste recommendations made by considering physical condition of daily garbage volume and land itself. The physical parameters of land include the distance to roads, distance to settlements and surface drainage obtained by image interpretation and field measurement. The results of this study indicate that remote sensing imagery can be used for data acquisition factors include the estimated volume of waste settlement patterns, size of houses, number of houses, the type of economic activity and the number of commercial buildings. The results of the estimated volume of waste in the city of Magelang is equal to 848.13 m3, with 731,52 m3 is volume of waste from residential and 116,61 m3 from commercial. The best locations are recommended construction of a new temporary waste result of processing the data using GIS in the Magelang city is Magelang Utara recommended 3 temporary waste capacity of 30 m3, 1 temporary waste capacity of 6 m3 and 1 temporary waste replacement. Magelang Tengah recommended 3 temporary waste capacity of 30 m3 and 4 temporary waste capacity of 6 m3. Magelang Selatan recommended 5 new temporary waste capacity of 30 m3, 3 temporary waste capacity of 6 m3 and 3 temporary waste replacement .